Dynamically Reconfigurable Control Struture for Three Phase Induction Motor Drives - Rajendran Ramasamy; Dr N Devarajan (Institute of Advanced Engineering and Science, 2012)
Field Programmable Gate Arrays (FPGAs) are a suitable hardware platform for the industrial control systems. These dynamically reconfigurable FPGAs can be used as an alternative digital solution to conventional microcontrollers and DSPs to ensure fast operation. This paper presents the feasibility of embedding the Direct Torque Control with Space Vector Modulation (DTC-SVM) of an induction motor into FPGA.The DTC-SVM of induction motor drives is simulated in a Matlab/Simulink environment using a Xilinx System Generator.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.183